Penguasaan dan Pengusahaan Tanah Oleh Warga Terhadap Aset PT Kereta Api Indonesia di Stasiun Klaten - Priscila Putri Haneswara; Rahayu Subekti; Purwono Sungkowo Raharjo (Universitas Sains dan Teknologi Komputer, 2023)
Land tenure by residents against PT KAI assets is found in several areas, one of which is in the Klaten Station area, the control raises questions about the legality of PT KAI in giving control to residents. this study aims to examine the legal review of land tenure and exploitation by residents against land owned by PT KAI at Klaten station. Researchers conducted research using empirical legal reasoning with descriptive properties based on primary data and secondary data by managing data from interviews and observations and then reasoning using applicable laws and regulations. Based on the research, it is concluded that land tenure by residents at the Klaten station is based on a lease agreement in the form of a lease on buildings and building leases with exploitation in the form of a residence and / or place of business. Land tenure can be lost based on the agreement of the parties but in its application it must fulfil the procedures in accordance with the agreement which if violated then the parties can conduct dispute resolution through deliberation and consensus but if it is not resolved then they can choose litigation or non-litigation methods.